2020
DOI: 10.5267/j.msl.2019.8.039
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of transformational leadership and entrepreneurial orientation on employee retention with moderating role of competitive

Abstract: This study aims to investigate employee motivational and environmental factors and their effects on employee retention and organizational performance. Employee retention is predicted by organizational environment, intrinsic motivation, organizational learning, knowledge management, entrepreneurial orientation, external connect and explained R 2 =76.3% of the variance in employee retention. Therefore, organizational performance is predicted by competitive advantage and employee retention and explained R 2 =19.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 42 publications
4
46
0
4
Order By: Relevance
“…This put on evidence the direct, indirect, and total effect of the variables [57]. In some studies [59][60][61], SEM analysis has been used to evaluate predictions and, as a result, the coefficient of determination (R 2 ) has been shown without the fit indexes that are commonly evidenced. Therefore, for the development of explanatory or predictive models, the variance portion can be used as a unique criterion to show the explanatory, or predictive, capacity in models that are developed with SEM.…”
Section: Discussionmentioning
confidence: 99%
“…This put on evidence the direct, indirect, and total effect of the variables [57]. In some studies [59][60][61], SEM analysis has been used to evaluate predictions and, as a result, the coefficient of determination (R 2 ) has been shown without the fit indexes that are commonly evidenced. Therefore, for the development of explanatory or predictive models, the variance portion can be used as a unique criterion to show the explanatory, or predictive, capacity in models that are developed with SEM.…”
Section: Discussionmentioning
confidence: 99%
“…The partial least square method was used to analyze the population of 317 statistical samples, and it was found that transformational psychological leadership had a greater impact on enterprise innovation than charismatic leadership. Yamin (2020) proposed that managers and policy makers should consider intrinsic motivation and transformational leadership in order to improve employee retention and organizational performance through effect scale analysis. The improvement of organizational learning ability is an important factor related to the future development of enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Competitive advantage is the ability of the organization to acquire, integrate and reconfigure its resources in response to growing and changing customer demands (Yamin, 2020). A company is said to have occupied a competitive advantage position if it has a competitive advantage in resources that can produce superior value at a low cost (Muhajirin & Kamaluddin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It grows from the company value that can create value for its buyers, exceeding its costs incurred for value creation (Widiastuti, 2016). It is achieved when the rate of economic profit is higher than the rate of competitors (Yamin, 2020). Based on the definitions, competitive advantage can be defined as outstanding capabilities of human resources in a company to utilize its unique resources to fulfill the needs and wants of the customers.…”
Section: Introductionmentioning
confidence: 99%